Physicochemical characterization of functional creamy candy from the fruit of juazeiro (Ziziphus joazeiro Mart.) (Research, Society and Development, 2022)
Sweets in paste and in pieces are considered products that help the development of the regions that produce them and are a good way of using and conserving the fruit. However, the scientific literature regarding the addition of probiotics in sweets is very scarce. The objective was to develop a functional creamy candy from the juazeiro fruit with the addition of fructooligosaccharide (FOS) and to explore its physicochemical and nutritional characteristics. Two formulations of creamy sweets were developed: DJP (control) containing only pulp, sucrose (60%) and lemon juice; and DJ1 containing pulp, sucrose (30%), FOS (10%) and lemon juice. The products were evaluated for physical-chemical and nutritional characterization. The moisture, ash, crude fiber, lipid and protein contents were higher (p